A 10-W High-Power Amplifier Using Input Nonlinearity for K-Band Satcom Applications - Yi, Chupeng; Lu, Yang; Zhao, Ziyue; Wang, Yuchen; Zhou, Jiuding; Zhao, Bochao; Li, Peixian; Ma, Xiaohua; Hao, Yue (IEEE microwave and wireless components letters, 2022)
This letter presents a K-band 0.1-μm GaN on Si 10-W high-power amplifier (HPA) for the downlink of the satellite communication system. The proposed HPA uses the driver-stage transistor to generate a half-sinusoidal waveform that is delivered to the power-stage transistor. The half-sinusoidal waveform combines the input nonlinearity of the power-stage transistor to simultaneously improve the efficiency and expand the design space of the input harmonic impedance. A simple and compact interstage matching network (ISMN) design is used to match the harmonic impedance of both driver and power-stage transistors to create the corresponding waveforms. The proposed HPA has a small size of 3.5 mm x 3.2 mm and operates in the frequency range of 17-20.5 GHz achieving a 22-dB gain, an average output power (P _{{out}}) of 42 dBm, and 41% power-added efficiency (PAE) in the pulsed measurement. Moreover, the proposed HPA maintains a PAE of more than 33% and output power of 40.4 dBm in continuous wave (CW) measurement.